Nonlinear dynamic response of ES-FGM plate under blast load - Cong, Pham Hong; Duc, Nguyen Dinh (Vietnam Journal of Mechanics, 2018)
The paper studies nonlinear dynamic response of an eccentrically stiffened FGM (ES-FGM) plates resting on the elastic foundations subjected to blast and thermal loads with temperature dependent material properties using the Reddy's higher order shear deformation plate theory, stress function, the Galerkin and the fourth order Runge-Kutta methods. The plates are reinforced by outside stiffeners and both stiffeners and plate are deformed under temperature. The effects of material and geometrical properties, temperature-dependent material properties, elastic foundations and stiffeners on the nonlinear dynamic response of the ES FGM plate under blast and thermal loads in thermal environments are studied and discussed.